STRATEGI PENGRAJIN BATIK TANAH LIEK MELALUI HOME INDUSTRI DALAM MENINGKATKAN EKONOMI - Indri Syafitri; Elvawati Elvawati; Hanafi Saputra (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
The existence of the Tanah Liek batik home industry in Dharmasraya Regency has been able to contribute to economic improvement for the batik craftsmen themselves. Their various strategies in improving their economy are very interesting to reveal, because in the last 3 years there has been an increase in income reaching 46%. Departing from this, the purpose of this article is to describe the strategies of Tanah Liek batik craftsmen through home industries in improving the economy. The approach used is a qualitative approach with a case study type. Data collection in this article was obtained by means of observation, interviews and document studies. Based on the habitus and capital theory proposed by Pierre Bourdieu, it is known that this research accumulates economic capital, cultural capital and social capital as a form of marketing strategy in improving the economy.Â Based on the results of the research that has been described, the strategy that continues to be applied by Tanah Liek batik craftsmen is solely to increase their economic level. The strategy used by the artisans continues to be improved all the time by always being open to the acculturation of economic, cultural, and social capital. This is continuously done by the craftsmen so that their production results are widely known in all circles and have an impact on the income they earn. In connection with the conclusions described in the previous paragraph, suggestions that can be submitted for the development of further research are: a). In addition to implementing several strategies that have been implemented, the home industry should also pay attention to the administrative management of incoming orders each month. It is intended that this home industry have clear data and archives. b). The government should continue to provide training and development related to skills, management, and administration related to cooperatives, small and medium enterprises, industry, and trade in Dharmasraya Regency so that it is able to continue to develop and be more highly competitive. c). For future researchers, it is suggested and expected that they will be able to develop this research even better. So that this research can be maximised for the future.